Evaluación de tres dosis de cianobacterias en el crecimiento del cultivo de papa (Solanum tuberosum) variedad súper chola en el cantón Mejía provincia de Pichincha 2023. - Loachamín Tipán, Andrés Leopoldo (2023)
In the investigation of "Evaluation of three doses of cyanobacteria in the growth of patato crops (Solanum tuberosum¡ super chola variety, it was executed in a completely randomized block design (DBCA), consisting of 4 treatments, each treatment with 3 repetitions giving a total of 12 experimental units with an area of 1200m2. In the field, the variables to be evaluated were: an increase in root mass in this study revealed, in the treatments T3 (Cyanobacteria), which includes a dose of l .25gr/l, with an average of 304.33gr, T2 with a dose of O, 5gr/l, with an average of 280.08gr, being the T3 (] .25gr/l) that obtained favorable results, root length of the T3 treatment with a <lose of l .25gr/l an average of 5. l 6cm, located this value of greater efficiency in the size of the root system, the treatment T3 (Cyanobacteria) with a dose of l .25gr/l, in this variable of number of shoots its average was 11.08, located this value in the first range of greater number of shoots. In this plant height variable, treatment T3 with a <lose of l .25gr/1 reached a height of 25.23cm and T2 with a <lose of 0.5gr/1 with an average height of22.77cm, in the variable of plant vigor for the T3 treatment an average of 2.20 is a vigorous plant, in this soil cover variable the T3 treatment 1.25gr/L an average 2.37 covers more than 50% of the soil, in tbis variable of habit of the plant in the treatment T3 1.25gr/1 an average of 2.57 is a semi-erect plant, in the senescence variable there is no great difference since the entire crop shows the same number of days elapsed from sowing to presenta green color and with first signs ofyellowing of upper leaves which was at 135 days.